Ozone pollution episodes and PBL height variation in the NYC urban and coastal areas during LISTOS 2019 - Yonghua Wu; Kaihui Zhao; Xinrong Ren; Russell R. Dickerson; Jianping Huang; Margaret J. Schwab; Phillip R. Stratton; Hannah Daley; Dingdong Li; Fred Moshary (Atmospheric Environment, 2024)

Inferred vehicular emissions at a near-road site: Impacts of COVID-19 restrictions, traffic patterns, and ambient air temperature - Dolly L. Hall-Quinlan; Hao He; Xinrong Ren; Timothy P. Canty; Ross J. Salawitch; Phillip Stratton; Russell R. Dickerson (Atmospheric Environment, 2023)

Mutagenicity of acrylamide and glycidamide in human TP53 knock-in (Hupki) mouse embryo fibroblasts - Lisa Hölzl-Armstrong; Jill E. Kucab; Sarah Moody; Edwin P. Zwart; Lucie Loutkotová; Veronica Duffy; Mirjam Luijten; Gonçalo Gamboa da Costa; Michael R. Stratton; David H. Phillips; Volker M. Arlt (Archives of Toxicology, 2020)
Acrylamide is a suspected human carcinogen formed during high-temperature cooking of starch-rich foods. It is metabolised by cytochrome P450 2E1 to its reactive metabolite glycidamide, which forms pre-mutagenic DNA adducts. Using the human TP53 knock-in (Hupki) mouse embryo fibroblasts (HUFs) immortalisation assay (HIMA), acrylamide- and glycidamide-induced mutagenesis was studied in the tumour suppressor gene TP53 . Selected immortalised HUF clones were also subjected to next-generation sequencing to determine mutations across the whole genome. The TP53 -mutant frequency after glycidamide exposure (1.1 mM for 24 h, n = 198) was 9% compared with 0% in cultures treated with acrylamide [1.5 ( n = 24) or 3 mM ( n = 6) for 48 h] and untreated vehicle (water) controls ( n = 36). Most glycidamide-induced mutations occurred at adenines with A > T/T > A and A > G/T > C mutations being the most common types. Mutations induced by glycidamide occurred at specific TP53 codons that have also been found to be mutated in human tumours (i.e., breast, ovary, colorectal, and lung) previously associated with acrylamide exposure. The spectrum of TP53 mutations was further reflected by the mutations detected by whole-genome sequencing (WGS) and a distinct WGS mutational signature was found in HUF clones treated with glycidamide that was again characterised by A > G/T > C and A > T/T > A mutations. The WGS mutational signature showed similarities with COSMIC mutational signatures SBS3 and 25 previously found in human tumours (e.g., breast and ovary), while the adenine component was similar to COSMIC SBS4 found mostly in smokers’ lung cancer. In contrast, in acrylamide-treated HUF clones, only culture-related background WGS mutational signatures were observed. In summary, the results of the present study suggest that glycidamide may be involved in the development of breast, ovarian, and lung cancer.

Younger age-at-diagnosis for familial malignant testicular germ cell tumor - Phuong L. Mai; Bingshu E. Chen; Kathy Tucker; Michael Friedlander; Kelly-Anne Phillips; David Hogg; Michael A. S. Jewett; Istvan Bodrogi; Lajos Geczi; Edith Olah; Ketil Heimdal; Sophie D. Fosså; et al. (Familial Cancer, 2009)